Serum biomarkers for the evaluation of liver fibrosis: The need for better tests - Müjdat Zeybel; Ramazan İdilman (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Zeybel M, İdilman R. Serum biomarkers for the evaluation of liver fibrosis: the need for better tests. Turk J Gastroenterol 2018; 29: 377-8.